Economic Integration and Financial Stability : A European Perspective - De Nicolo, Gianni (IMF Working Papers; Working Paper, 2006)
This paper assesses changes in synchronization of real activity and financial market integration in Western Europe and evaluates their implications for financial stability. We find increased synchronization of real activity since the early 1980s and increased equity markets integration since the early 1990s. We also find that measures of systemic risk at large European financial institutions have not declined during the period 1990-2004 and that bank systemic risk profiles have converged. At the same time, the sensitivity of bank and insurance systemic risk measures to common real and financial shocks has increased in most countries. Overall, these results suggest that the integration process does not necessarily entail an unambiguously positive effect on financial stability.